Airway proteases: an emerging drug target for influenza and other respiratory virus infections - Laporte, Manon (Curr Opin Virol, 2017)
To enter into airway epithelial cells, influenza, parainfluenza- and coronaviruses rely on host cell proteases for activation of the viral protein involved in membrane fusion. One protease, transmembrane protease serine 2 (TMPRSS2) was recently proven to be crucial for hemagglutinin cleavage of some human influenza viruses. Since the catalytic sites of the diverse serine proteases linked to influenza, parainfluenza- and coronavirus activation are structurally similar, active site inhibitors of these airway proteases could have broad therapeutic applicability against multiple respiratory viruses. Alternatively, superior selectivity could be achieved with allosteric inhibitors of TMPRSS2 or another critical protease. Though still in its infancy, airway protease inhibition represents an attractive host-cell targeting approach to combat respiratory viruses such as influenza.